Moringa oleifera Lam.: A Valuable Medicinal Plant, Boon of Nature (International Journal of Ayurveda and Pharma Research, 2022)
Moringa oleifera Lam., is often referred to as “The Miracle Tree” due to its highly utility and it is said that every part of this tree have beneficial properties that can serve humanity. Moringa oleifera Lam., is native to the Indian sub-continent and naturalized in tropical and sub tropical areas around the world. It is very important and highly valuable medicinal plant. It has impressive range of different pharmacological action of various parts of this plant such as leaves, roots, seeds, bark, pods, flowers shows anti-bacterial, anti-inflammatory, anti-fungal, antispasmodic, antipyretic, hypotensive, cholesterol lowering, anti-diabetic, anti-biotic etc. activity. Different parts of this plant contain a unique combination of important nutritional minerals, vitamins, amino acids, ß-carotene, and various phenolics. It is widely used for medicinal and therapeutically with its high nutritional value in the indigenous system of medicine. The aim of present review study is to explore the importance of Moringa oleifera Lam., to reveal the nutritional and medicinal properties of this plant and summarize scientific evidence of pharmacological properties that supports the value and multifunctional uses.